Islamic Education Public Relations Management: Functions and Code of Ethics - Dede Asrori Rohim; Tika Widiyan Widiyan; Hendriadi Hendriadi Hendriadi (Peneliti.net, 2022)
The purpose of this paper is to examine the function and code of ethics of public relations management in Islamic educational institutions. The research methodology used is library research with data sources coming from books, journals, and all literature that discusses public relations management. meanwhile the data analysis technique used is content analysis, namely analyzing all the literature that is used as a data source. The result of this research is that public relations management is the whole process of activities that are planned and endeavored intentionally and seriously, accompanied by continuous guidance to gain sympathy from the community in general, and in particular the people who have a direct interest in the school. The function of public relations management is as a provider of information and intermediary/liaison between the organization and the community. In implementing public relations, it is inseparable from the application of ethics which is the basis for implementing public relations, a public relations practitioner must be trustworthy in conveying and receiving information, fair in determining all cases, and keeping promises in the relationships that have been established between the organization and its community.